2014
DOI: 10.1103/physrevb.90.085123
|View full text |Cite
|
Sign up to set email alerts
|

Suppression ofTCby overdoped Li in the diluted ferromagnetic semiconductorLi1+y(Zn<

Abstract: We use muon spin relaxation (μSR) to investigate the magnetic properties of a bulk form diluted ferromagnetic semiconductor (DFS) Li 1.15 (Zn 0.9 Mn 0.1)P with T C ∼ 22 K. μSR results confirm the gradual development of ferromagnetic ordering below T C with a nearly 100% magnetic ordered volume. Despite its low carrier density, the relation between static internal field and Curie temperature observed for Li(Zn,Mn)P is consistent with the trend found in (Ga,Mn)As and other bulk DFSs, indicating these systems sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 27 publications
(52 reference statements)
2
24
0
1
Order By: Relevance
“…the "111" type Li(Zn,Mn)As、 "122" type (Ba,K)(Zn,Mn) 2 As 2 and "1111" type (La,Ca)(Zn,Mn)SbO, which are named by the chemical ratio of their parent phases. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Among these new DMSs, the ThCr 2 Si 2 type (Ba,K)(Zn,Mn) 2 As 2 has a Curie temperature (Tc) up to 230 K which marks the current reliable record Tc for DMSs where ferromagnetism is mediated by carriers. [12][13] The (Ba,K)(Zn,Mn) 2 As 2 is believed to be one of milestone materials for the research of DMSs.…”
Section: Introductionmentioning
confidence: 99%
“…the "111" type Li(Zn,Mn)As、 "122" type (Ba,K)(Zn,Mn) 2 As 2 and "1111" type (La,Ca)(Zn,Mn)SbO, which are named by the chemical ratio of their parent phases. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Among these new DMSs, the ThCr 2 Si 2 type (Ba,K)(Zn,Mn) 2 As 2 has a Curie temperature (Tc) up to 230 K which marks the current reliable record Tc for DMSs where ferromagnetism is mediated by carriers. [12][13] The (Ba,K)(Zn,Mn) 2 As 2 is believed to be one of milestone materials for the research of DMSs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown from NMR20 and μ SR measurements that the ferromagnetism in (BaK)(ZnMn) 2 A s 2 9, Li(Zn, Mn)As10, (La, Ba)(Zn, Mn)AsO12 and Li(Zn, Mn)P21 are homogeneous, i.e., the long range ferromagnetic ordering is arising from the Mn atoms doped at Zn sites, instead of Mn related magnetic impurities. Furthermore, μ SR results demonstrated that these bulk form DMSs share the same mechanism for the ferromagnetic ordering as that of (Ga, Mn)As22.…”
mentioning
confidence: 99%
“…After this discovery, several new types of bulk forms of DMSs with decoupled spins and charges injections have been reported. [17][18][19][20][21][22][23][24][25][26][27] The availability of bulk forms of specimens make it possible to investigate the microscopic magnetism of DMSs based on typical bulk probes, 28 such as nuclear magnetic resonance (NMR), 29 muon spin relaxation (µSR), 17,18,20,30 neutron scattering, absorption spectroscopy (XAS), 31 resonance photoemission spectroscopy (RPES), 31 and angle-resolved photoemission spectroscopy (ARPES). 32 It has been confirmed by the XAS measurements that the valence of Mn in (Ba,K)(Zn,Mn) 2 As 2 is bivalence.…”
Section: Introductionmentioning
confidence: 99%